Effect of Different Lipid Ratios on Physicochemical Stability and Drug Release of Nanostructured Lipid Carriers Loaded Coenzyme Q10 - Abdulloh Suyuti; Esti Hendradi; Tutiek Purwanti (Universitas Airlangga, 2023)
Background: For treatment or skin care via topical route, Coenzyme Q10 needs to permeate the epidermis which it is practically insoluble in water and a high molecular weight that make it difficult to penetrate the skin. Nanostructured Lipid Carriers (NLC) is chosen because of its ability to dissolve and solve the problem of low skin permeation. The type and ratio of solid and liquid lipids used in NLC affect the physicochemical characteristics, thus affecting the release profile and system stability. Objective: This study aimed to determine the effect of various ratios of Compritol 888 ATO as solid lipid and Miglyol 812 as liquid lipid on the physicochemical stability and Coenzyme Q10 release profile of NLC system. Methods: NLC was prepared using High Shear Homogenization method with three different lipid ratios. The ratio of Compritol 888 ATO : Miglyol 812 was 70:30, 80:20, and 90:10, respectively. NLC was evaluated for drug release and stability parameters including organoleptic, particle size, polydispersity index (PI), pH, viscosity, assay, and entrapment efficiency. Results: The stability test result for 90 days showed increments in the particle size and viscosity, whereas for assay and entrapment efficiency were decreased. The release test results showed no significant difference in the release parameters of the three tested formulas. Conclusion: During stability evaluation, NLC-CoQ10 systems did not significantly change pH and PI values, but statistically significantly changed particle size, viscosity, assay, and entrapment efficiency. The different in lipid ratios used in the formulas did not show significantly different results for release parameters.